Casca do jambolão: caracterização, planejamento e desenvolvimento de embalagens biodegradáveis ativas - Neves, Bruna Stephanny Santos (2017)
The high production of fruit of jambolão (Syzygium cumini) during the harvest and the lack of information about its processing emphasize the development of new technologies for the processing of this fruit, since it has been proven that different parts of this fruit have functional properties. The objective of this work was to characterize and extract antioxidant and antimicrobial compounds from the shell of the powdered jambolão, by means of a complete factorial experimental design, in order to obtain an optimized extract (EO), which was later incorporated in bio-degradable packages. For this, initially the fruit was pulped and separated the pulp and bark fractions, where a batch of bark was submitted to drying at 40 ° C to obtain the powder. The three samples were characterized physicochemically and as to the content of bioactive compounds. Twelve extracts were produced from the powder, based on an experimental design 32, which were evaluated for anti-oxidant activity (ABTS +, DPPH, FRAP) and antimicrobial (Disk diffusion, MIC) for seven strains of microorganisms. The results were analyzed by response surface methodology, in order to optimize the best extraction condition, on which total phenolic compounds (CFT), total flavonoids (FT) and total monomeric anthocyanins (TMA) were analyzed. Different EO proportions were then incorporated into cellulose acetate and starch films with chitosan and these were characterized in terms of color, antioxidant and antimicrobial properties in vitro. It was observed that the levels of CFT, FT, TMA and total antioxidant activity of the peel were about ten times higher than those of the pulp. In addition, it was verified that all the extracts produced with the flour had high antioxidant activity and were effective against the microorganisms Staphylococcus aureus and Listeria monocytogenes and the best response was obtained when using 70% ethanol and 1:10 sample: solvent ratio. In the EO, results were obtained from 36.50mg GAE / g for CFT, 1.94mg QE / g for FT, 1269 mgCE / 100g for TMA and 40.0mg AAE / 100g for Ascorbic Acid.Regarding the films, it was observed that in different EO concentrations, there was a significant difference in color of the treatments when compared to the control in both bases. As for the antioxidant activity of biofilms, it was observed that in the DPPH and FRAP methods, all treatments varied among them, except in the ABTS method. This activity was proportional to the concentration of EO applied, however, in the cellulose films a greater increase was verified in relation to the control, when compared to the starch. It was also verified that only the biofilms of starch presented inhibitory effects, being obtained for S. aureus from 20% of the EO, and for L.monocytogenes in a concentration equal to or greater than 40% of EO, soon this showed itself moreresistant. Thus, the richness of compounds exhibited by Jamelão peel powder, which when applied in packages, became once normal matrices in active, especially with respect to the antioxidant aspects.